Meningkatkan Kemampuan Representasi Semiotik Siswa Dengan Metode Guided Discovery Learning - Christine Wulandari Suryaningrum; Alifiah Farindra Marta Rini; Lady Agustina; Novy Eurika (Universitas Islam Jember, 2023)
This classroom action research aims to improve the ability of students' semiotic representations on material tangents to circles at SMP Muhammadiyah 3 Rambipuji. The preliminary study stated that 20% of class VIII students were able to represent their thinking results in the form of images and symbols. Ten grade VIII students became the research subjects. Data collection was carried out by field observations, student worksheets, and interviews. Data analysis with the stages of data reduction, data presentation, and drawing conclusions. Each cycle has 4 stages, namely, making plans, implementing action plans, making observations, and reflecting on research results. In this study, it was said to be successful if at least 85% of students obtained scores that exceeded the KKM limit. From the results of the implementation of cycle 1, 60% of students were able to represent the answers to the questions in the semiotic representation of the research subjects. Cycle 2 following the guided discovery learning method, indicates the development of semiotic representation abilities. Students find it easier to represent a problem in material tangent to a circle. So that the final value obtained has increased significantly is 90%. Keywords: Guided Discovery Learning, Semiotic Representation